The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1142/s0218271817500316
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of modified Chaplygin gas inflation on the Brane with bulk viscous pressure

Abstract: We investigate the role of bulk viscous pressure on the warm inflationary modified Chaplygin gas in brane-world framework in the presence of standard scalar field. We assume the intermediate inflationary scenario in strong dissipative regime and constructed the inflaton, potential, entropy density, slow-roll parameters, scalar and tensor power spectra, scalar spectral index and tensor-to-scalar ratio. We develop various trajectories such as n s − N , n s − r and n s − α s (where n s is the spectral index, α s … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Moreover, many authors have investigated the warm inflation in various alternative as well as modified theories of gravity [37][38][39][40][41][42][43][44][45][46][47][48][49]. Recently, a new family of inflation models is being developed named shaft inflation [50].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many authors have investigated the warm inflation in various alternative as well as modified theories of gravity [37][38][39][40][41][42][43][44][45][46][47][48][49]. Recently, a new family of inflation models is being developed named shaft inflation [50].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in Ref. [26], the dynamics of warm inflation in a modified Chaplygin gas (MCG) was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Panotopoulos and Videla [26] discussed the warm inflation by assuming the quartic potential and an inflaton decay rate proportional to temperature and found that their results are in agreement with the latest Planck data, obtaining a lower value for the tensor-to-scalar ratio compared to the cold inflation scenario. Going further, several authors have investigated the warm inflation scenario in various alternative/modified theories of gravity [27,28]. Moreover, a new family of inflation models is being developed named as shaft inflation [29].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have examined warm inflation by considering the Chaplygin gas, standard and tachyon scalar field models in Einstein's General Relativity as well as in braneworld scenario with different expressions for the dissipative coefficient [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. They found the consistency of their results with observational data, i.e., BICEP2, WMAP (7 + 9) and Planck data.…”
Section: Introductionmentioning
confidence: 99%